Is cognitive case formulation science or science fiction? - Bieling, P; Kuyken, W (2003)
As with all systematic models of therapy, cognitive therapy distills a theory to the understanding of particular cases through the case formulation method. This article sets out criteria to evaluate whether cognitive case formulation follows the process of scientific inquiry, and it questions whether the formulation method meets these criteria. In terms of the evidence base for the cognitive theory that underpins cognitive case formulation, the research suggests that although the descriptive elements of cognitive theory are substantiated, the explanatory elements have received less support. In terms of the scientific status of the cognitive case formulation process, current evidence for the reliability of the cognitive case formulation method is modest, at best. There is a striking paucity of research examining the validity of cognitive case formulations or the impact of cognitive case formulation on therapy outcome. Implications for the clinical use of cognitive case formulation within a scientist-practitioner model are discussed, and potential programs of research to evaluate the case formulation method are described. © 2003 American Psychological Association D12.